Psycholinguistic Analysis of Anthroponyms - Hakimovna, Alpanova Shirinkhon (European Journal of Life Safety and Stability (2660-9630), 2021)
The article discusses the spiritual, cultural, social features of anthroponyms and provides their psycholinguistic analysis. Aspects of anthroponyms related to national character, aspects related to human psychology are covered.